Cost effectiveness of using trastuzumab biosimilars compared to trastuzumab original drugs to treat breast cancer in a hospital setting - Eric C. Barat; Marianne L.E. Arrii; Annaelle Soubieux-Bourbon; Mikaël Daouphars; Rémi Varin; Patrick R. Tilleul (Breast, 2023)
Introduction: Subcutaneous (SC) drug administration, such as the Herceptin® in an oncology day hospital reduces the administration time of trastuzumab. In the context of combination therapy administration, this time-saving may be called into question. The challenge posed by the deployment of much less expensive IV biosimilar forms raises questions about the cost-effectiveness of SC administration. Methods: Using data from a french Diagnostic Related Groups regarding prescriptions of intravenous Herceptin® (HIV), Herceptin® biosimilar IV (BSIV), and Herceptin® subcutaneous (HSC), we conducted two simulations. This simulation involved replacing all HSC with BSIV in combination therapy administration (Simulation 1) and subsequently substituting IV forms with SC forms only when prescribed as monotherapy (Simulation 2). A cost-benefit analysis was conducted based on these two simulations, from the hospital's perspective, for Normandy's population over a 1-year timeframe. Results: In Simulation 1, there was an average cost-saving of €12 per patient per year, but it resulted in a loss of 10140 min, equivalent to 10 min per patient per year when compared to the current situation. Simulation 2 yielded average cost-savings for the hospital amounting to €51 per patient per year, along with a time-saving of 67 min per patient per year compared to the current situation. Conclusions: The development of a program aimed at optimizing the prescription of Trastuzumab holds the potential to deliver significant cost-savings to hospitals while enhancing the quality of service provided to the patients. This optimization involves using H SC in monotherapy and BS IV in combination therapy administration.